2021
DOI: 10.1037/drm0000181
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for preferentially dreaming of waking-life experiences that are relevant to one’s life story.

Abstract: The continuity hypothesis of dreaming proposes that waking-life experiences can be incorporated into dreams. On the other hand, it is proposed that dreams may reflect the process of sleep-dependent consolidation for autobiographical memories. A model of autobiographical memory emphasizes the self's role and goals in remembering. Based on this model, we hypothesized that waking-life experiences that are relevant to one's life story are preferentially incorporated into dreams. Participants (N = 30) kept daily lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 34 publications
(50 reference statements)
1
7
0
Order By: Relevance
“…First, in line with our hypothesis and previous experimental research on the role of autobiographical memory in dreaming (Grenier et al, 2005; Malinowski & Horton, 2014a, 2014b; Wang et al, 2021), we found that individuals who report that they generally remember their past well and have vivid and clear recollections of the past (i.e., higher scores on the ART) were more inclined to experience their dreams as meaningful, vivid, entertaining, and as reflections of their past, present and future (i.e., higher scores on the IDEA dimensions of dream significance, recall, entertainment, guidance and continuity). These findings provide a new perspective on the relation of dreams to autobiographical memory by showing that not only does dreaming reflect the content of specific autobiographical memories, but also that the way people generally remember their personal past is closely associated with their general dream experiences.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…First, in line with our hypothesis and previous experimental research on the role of autobiographical memory in dreaming (Grenier et al, 2005; Malinowski & Horton, 2014a, 2014b; Wang et al, 2021), we found that individuals who report that they generally remember their past well and have vivid and clear recollections of the past (i.e., higher scores on the ART) were more inclined to experience their dreams as meaningful, vivid, entertaining, and as reflections of their past, present and future (i.e., higher scores on the IDEA dimensions of dream significance, recall, entertainment, guidance and continuity). These findings provide a new perspective on the relation of dreams to autobiographical memory by showing that not only does dreaming reflect the content of specific autobiographical memories, but also that the way people generally remember their personal past is closely associated with their general dream experiences.…”
Section: Discussionsupporting
confidence: 88%
“…This factor showed that the tendency to consider one’s personal memories to be vivid, as well as coherent and relevant to one’s life story and identity, was associated with the tendency to experience meaningful and self-relevant dreams. Given that people typically rely on their autobiographical memories to construct their sense of identity, life story, and meaning in life (Conway & Pleydell-Pearce, 2000), and that dreams often include fragments of personally relevant autobiographical memories (Wang et al, 2021), it might be that, for some people, dreaming is an essential part of their identity, life story, and life meaning construction. This notion remains understudied and may be of interest for future work (Morewedge & Kupor, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This kind of method has been used by some research (e.g., Eichenlaub et al, 2019; J. E. Malinowski & Horton, 2014; van Rijn et al, 2015; Wang, Feng, & Shen, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…As observed for memory reactivations, dreams preferentially incorporate novel [68,69], emotionally intense (e.g., [70,71]), and personally meaningful (e.g., [40,72]) experiences.…”
Section: Selectivitymentioning
confidence: 76%